THE MADINAH CHARTER AS A CULTURE AND CIVILIZATION CONCEPT - Yani, Ahmad (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2021)
Efforts to build a modern civilized society by upholding human values ​​and justice were pioneered by the Prophet Muhammad long before the UN Universal Declaration of Human Rights in 1948, the French Revolution of 1789 or the birth of the American constitution in 1776. Prof. HAR Gibb in his book Writer Islam states,